Diversification of livelihoods of rural families and its relevance for the agro-ecosystems of El Paraíso (Honduras) and Jalapa (Nicaragua) - Pinoth Arguijo, Rut E. (2011)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2011